IMPLEMENTASI BIMBINGAN DAN KONSELING EDUKASI POLA ASUH ANAK PADA KOMUNITAS PENGAJIAN IBU-IBU KAMPUNG CIBODAS - Anggraeni, Peni; Prabowo, Arga Satrio; Nurmala, Meilla Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to provide education and psychological counseling to mothers in applying effective parenting patterns based on Islamic values. This is motivated by the high level of parental anxiety regarding their children's mental health. This study uses an approach consisting of community education, training, and coaching. The stages of implementation include: (1) Need assessment, (2) Development of educational modules and media, (3) Implementation of group education and counseling, (4) Coaching on parenting styles, (5) Evaluation of activities. The research subjects were 33 mothers who were members of the Cibodas Village Mothers' Study Group and had children ranging in age from toddlers to early elementary school age. The results of the activity showed that the implementation of the community service program was able to increase the participants' knowledge and readiness in applying positive parenting and empathetic communication withi the family.